Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.21608/jssae.2013.51785
|View full text |Cite
|
Sign up to set email alerts
|

Response of Some Wheat Varieties to Nitrogen Fertilization

Abstract: Two field experiments were conducted at Sakha Agricultural Research Station Farm, Kafr El-Sheikh Governorate, Egypt (31 o 05 ' N latitude and 30 o 56' E longitude) during 2009/2010&2010/2011 winter seasons to investigate the response of some wheat varieties to different N levels. Split plot design with four replicates was applied, the main plots were assigned to four wheat varieties, Gimiza 9, Giza 168, Sakha 61 and Sakha 93. The subplots were assigned to four nitrogen levels of 0, 30, 60 and 90 kg N/fed. (fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
(9 reference statements)
3
10
0
Order By: Relevance
“…These findings might be attributed to the differences in their genetical constitution and genetic factors makeup. These results are in agreement with those detected by Harb et al (2012), Haroun, Samia et al (2012), Atia and Ragab (2013) and Lak et al (2013).…”
Section: Effect Of Sowing Datessupporting
confidence: 93%
See 1 more Smart Citation
“…These findings might be attributed to the differences in their genetical constitution and genetic factors makeup. These results are in agreement with those detected by Harb et al (2012), Haroun, Samia et al (2012), Atia and Ragab (2013) and Lak et al (2013).…”
Section: Effect Of Sowing Datessupporting
confidence: 93%
“…Thus, Gemmeiza 9 gave the highest values of heading date, plant height, number of spikes/m 2 , 1000-grain weight, grain, straw and biological yields/fed. Atia and Ragab (2013) found that wheat cultivars significantly differed in grain and straw yields, as well as protein content. Gemmeiza 9 cultivar had the highest mean value of grain and straw yields, protein content of grains.…”
Section: Introductionmentioning
confidence: 96%
“…Harb et al (2012) revealed that Gemmeiza 9 cultivar exceeded Sakha 93 cultivar significantly in number of spikes/m 2 , weight of grains/spike, number of grains/spike, 1000-grain weight and grain yield/fed. Atia and Ragab (2013) found that Gemmeiza 9 cultivar had the highest values of grain and straw yields as well as protein and potassium contents in grains. Seleem and Abd El -Dayem (2013) showed that the highest significant value of grain yield was obtained by Gemmeiza 9 followed by Misr 1 then Sakha 94 and Giza 168.…”
Section: Introductionmentioning
confidence: 92%
“…This leads to a widespread over-use of nitrogen to improving growth characters, consequently, maximization wheat production as well as quality parameters. Many researchers decided that using nitrogen fertilizer in suitable needed level could improve growth, yield and its components as well as quality of wheat, including Seadh et al (2009), Abedi et al (2010), Tababtabaei and Ranjbar (2012), Atia and Ragab (2013), Haileselassie et al (2014), Khan et al (2014), Seadh and Abido (2014) and Seadh and El-Metwally (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, NPK uptake of grain and straw were significantly increased (Antoun et al, 2010). Grain and straw yields/fed and protein content were significantly increased by increasing nitrogen fertilizer levels from 0 to 30, 60 and 90 kg N/fed (Atia and Ragab, 2013). Mineral fertilizing with 100 % of the recommended rate i.e.…”
Section: Introductionmentioning
confidence: 96%